VIM-5 metallo-?-lactamase-producing Pseudomonas putida from Turkey - Poirel, Laurent; Yakupogullari, Yusuf; Kizirgil, Ahmet; Dogukan, Muruvvet; Nordmann, Patrice (Elsevier Science Bv, 2009)
[Abstract Not Available]
Keywords: Aeruginosa Clinical Isolate